Natural Products and Traditional Medicine: Investigating the Role of Natural Products and Traditional Medicine in Modern Pharmacology - Singh, Shekhar; Rai, Vishal; Kanojia, Akanksha; Yadav, Ajay (Journal for Research in Applied Sciences and Biotechnology, 2024)
Natural products and Traditional medicines have been in the use for effective management of diseases and care of human suffering for the last thousands of years and are depicted to contain a vast database of Bioactive molecules of immense therapeutic significance. The following paper’s purpose is to reflect on these practice in arts of pharmacology with regards to their history, origin, operation, and challenges in the modern world. These are plant compounds, animal, and minerals and how they have been used in former time and even in this 21st century. Modern trends and novel approaches suggest that new technologies in the genomics, proteomics and metabolomics will change the direction of the natural products research emphasizing molecular targeting as well as the individual approach towards patient treatment. It also talks about the problems of standardization and quality of the work done; therefore there is a great emphasis on the clinical trial they also go further to address rules that govern the application of such technologies. Secondly, the expansion in the usage of complementary medicine and integrative approach with natural substances in treating diseases, as well as attempts to educate doctors and other healthcare practitioners on the merits of traditional medicine. Hence, the focus of future prospects continues to be laid on advanced technologies and the role of global multilateralism in progress and regulation. The author has demonstrated a lot more about modern pharmacology within this review and is making a call for assimilation of the modern discovery with native knowledge for the benefit of mankind.